2010
DOI: 10.1645/ge-2060.1
|View full text |Cite
|
Sign up to set email alerts
|

Avian Malaria Parasites Share Congeneric Mosquito Vectors

Abstract: Assessing parasite specificity to vector is crucial to understanding the emergence of vector-borne diseases and the evolution of parasite diversity. Avian malaria parasites have a cosmopolitan distribution and broad avian host range, which together predict they are vector generalists, but little is known about parasite-vector associations in the wild. We tested this prediction by asking if 5 different mosquito species, known to feed on birds and abundant in the northeastern United States, were naturally infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 60 publications
5
87
1
2
Order By: Relevance
“…Previous research has demonstrated that these Culex species are known avian malaria vectors [25] and are infected with many of the same avian Plasmodium lineages [36]. Little information exists on the vectorial capacity of A. vexans.…”
Section: (C) Resolving Parasite -Bird and Parasite-mosquito Relationsmentioning
confidence: 99%
“…Previous research has demonstrated that these Culex species are known avian malaria vectors [25] and are infected with many of the same avian Plasmodium lineages [36]. Little information exists on the vectorial capacity of A. vexans.…”
Section: (C) Resolving Parasite -Bird and Parasite-mosquito Relationsmentioning
confidence: 99%
“…This new animal model associates the avian malaria parasite Plasmodium relictum (SGS1 lineage) and its natural vector, the mosquito Culex pipiens [13,14]. We carried out two different experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Specialized associations between specific parasites and vectors (20)(21)(22) may drive such heterogeneity, although a recent analysis suggests that parasitehost compatibility is also important (23), and local coevolutionary relationships between parasites and their hosts likely influence geographic distributions of both host and parasite populations (11,14,15). However, most regional studies of these parasites have focused on individual host species (24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%